Impact of a digital application on HbA1c levels in people with diabetes: a randomized controlled trial - Roth, Lena; Steckhan, Nico; Schwarz, Peter E. H. (Frontiers in Digital Health, 2025)
AimsDigital applications have the potential to enhance diabetes management, particularly in patients treated with insulin. This study aims to evaluate the impact of a digital application on self-management (ESYSTA, Germany), expressed in a change in HbA1c levels, in people with diabetes treated with insulin.Materials and methodsA randomized controlled, multicentric trial was conducted in 204 people with diabetes (60% type 2 diabetes) treated with insulin to assess the efficacy of ESYSTA. Participants were randomly assigned to either the intervention group (IG) using ESYSTA in addition to the German standard of Care (SoC) according to the German disease management programs (DMP) for 6 months or a control group (CG) receiving SoC only. The primary endpoint was the change in HbA1c levels. Secondary endpoints included well-being and diabetes-related distress.ResultsA clinically relevant reduction in HbA1c levels of on average −0.48% points (−0.66; −0.29) was observed in the IG after 6 months. Compared to the CG, this reduction was more pronounced, especially in the per-protocol sample [mean difference, −0.28% points; 95% CI (−0.54; −0.02)]. Improvements in the IG in further secondary endpoints, such as well-being or diabetes-related distress, indicate enhanced overall glycemic control and patient satisfaction in the IG.ConclusionsThe use of ESYSTA improved HbA1c levels and other secondary outcomes in people with diabetes who are treated with insulin in comparison with German SoC in the context of DMP. These findings support the integration of digital tools in routine diabetes care to optimize patient outcomes.Clinical Trial Registrationhttps://drks.de/search/de/trial/DRKS00025996, identifier DRKS00025996.